2003
DOI: 10.1097/01.pgp.0000092156.33490.89
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic Liposarcoma of the Uterus: Case Report and Literature Review

Abstract: A 62-year-old woman with a history of breast carcinoma being treated with tamoxifen presented with a rapidly enlarging pelvic mass. Imaging studies suggested a uterine leiomyoma with possible sarcomatous transformation. Laparotomy revealed a 15-cm, oval, well-circumscribed mass emanating from the posterior cervix and left uterosacral ligament. The tumor had a variegated fleshy, tan, myxoid, and necrotic sectioned surface. Microscopic examination revealed a variety of patterns and cell types characteristic of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
1
16
0
2
Order By: Relevance
“…Abnormal vaginal bleeding was the most common presentation, 4,14,25,31,41,43 and other symptoms included pelvic pain, increasing abdominal girth, dysuria, weight loss, and constipation. 4,14,18,20,39 Only 1 of 3 of our patients presented with uterine bleeding. The diagnoses of the previously reported 10 uterine liposarcomas were based strictly on histopathologic and immunohistochemical findings.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Abnormal vaginal bleeding was the most common presentation, 4,14,25,31,41,43 and other symptoms included pelvic pain, increasing abdominal girth, dysuria, weight loss, and constipation. 4,14,18,20,39 Only 1 of 3 of our patients presented with uterine bleeding. The diagnoses of the previously reported 10 uterine liposarcomas were based strictly on histopathologic and immunohistochemical findings.…”
Section: Discussionmentioning
confidence: 81%
“…To date, 10 cases within the uterus 4,14,18,20,25,31,32,39,41,43 have been described in the literature. Patients with uterine liposarcomas have ranged in age from 23 to 78 (mean, 56) years, which is similar to the age range found in our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One leiomyosarcoma was reported arising from a lipoleiomyoma (7). Liposarcoma of the uterus is rare; one case report found that it is histologically similar to its soft tissue counterpart, showing myxoid/round cell, storiform/pleomorphic, epithelioid, and spindle cell components (8). More common than pure liposarcoma of the uterus is endometrial carcinosarcoma (malignant mixed mullerian tumor) with heterologous liposarcomatous differentiation, a tumor that may on occasion be predominated by or completely overgrown by the liposarcomatous component.…”
Section: Resultsmentioning
confidence: 97%
“…Various lesions have been reported as causing distortion or swelling of the uterosacral ligament. These include endometriotic lesions, peritoneal pregnancy, ectopic ovarian tissue, cystic teratoma [8], liposarcoma [9], ependymoma [10], endomyometriosis [11], midgut carcinoid tumour [12], and metastatic deposits of local malignancies, such as cervical carcinoma [13,14].…”
Section: Discussionmentioning
confidence: 99%